Co-firing potential of raw and thermally treated Phyllostachys aurea bamboo with coal. Issue 10 (18th May 2016) - Bada, S. O.; Falcon, R. M. S.; Falcon, L. M.; Bergmann, C. P.
ABSTRACT: Thermogravimetric (TG) and differential thermogravimetric (DTG) analyses were used to assess the thermal behavior of raw bamboo Phyllostachys aurea (PA) and thermally treated PA under the conditions equating to torrefaction and low-temperature carbonization. The thermally treated products were blended with coal A and subjected to thermal analyses at temperatures ranging from 25 to 900°C. All samples were characterized in terms of their elemental composition (CHON and S), calorific value, and chemical structure using Fourier transform infrared spectroscopy (FTIR). The results revealed that the ignition temperature and devolatilization of the raw PA occurred earlier than coal A and the thermally treated bamboo, thus indicating higher fuel reactivity in the raw form. Raw PA was found to have a calorific value of 18.01 MJ/kg, whereas torrefied and low-temperature carbonized PA produced fuels with 20.60 and 27 MJ/kg, respectively. The thermal profiles of the thermally treated samples, when blended with coal, provided an insight into the co-firing compatibility of the fuels.